Interval Walking Training for Functional Optimization and Health in The Elderly: A Narrative Review - Ishad, Muhammad Raihan; Rahman, Farid (Academic Physiotherapy Conference Proceeding, 2025)
Introduction: The global rise in the older adult population presents challenges in maintaining their functional capacity and health. Aging is associated with declines in physical function, cardiovascular fitness, and metabolism, affecting quality of life. Interval Walking Training offers an adaptive, affordable, and safe exercise option to address these issues.Aim of the Study: This review aims to identify the benefits of Interval Walking Training in optimizing physical function and health in older adults and evaluate protocol variations and their effects.Methods: This narrative review includes seven studies published in the last ten years (2015–2025) and evaluates the effects of Interval Walking Training on various aspects of elderly health. Literature sources were obtained from PubMed, Cochrane, and Google Scholar using the keywords "Interval Walking Training," "Elderly," "Health," and "Functional Mobility."Results: Interval Walking Training consistently shows improvements in VO2max, walking speed, flexibility, and blood pressure and blood glucose control. Several studies also report improvements in quality of life. Although the effects on cognitive function are inconsistent, Interval Walking Training is considered safe, flexible, and reasonably compliant.Conclusion: IWT is a promising exercise alternative for older adults in the community and clinical settings. In the future, long-term studies with more homogeneous designs are still needed to strengthen the evidence and develop optimal protocols.